International handbook of workplace trauma support - Cooper, Cary L.; Hughes, Rick , 1967-; Kinder, Andrew (Wiley-Blackwell, 2012)
"The International Handbook of Workplace Trauma Support provides a comprehensive overview of contemporary standards and best practice techniques for organizations that draws from the latest research findings and experience of clinicians, academics, practitioners, and other leading authorities on trauma support from around the world"